Building Customer Citizenship Behavior from Relationship Quality and Perceived Value Perspective in Online Transportation Service - Tatik Suryani; Indra Listyarti (Jurnal Sosial Humaniora, 2020)
Recently, Customer Citizenship behavior (CCB) has become a research focusin marketing. However, not many researches focus on the antecedent of thisvariable from the marketing behavior perspective. The research objective isto examine the effect of Relationship Quality and Perceived Value on CCB inonline transportation services and Customer Satisfaction as the mediation inthis relationship. The research involved 400 online transportation customersin Indonesia who used a minimum of three times in this transportation. Byusing Partial Least Square (PLS), the result found that Relationship Qualityhas a significant positive effect on Customer Satisfaction and CCB, PerceivedValue has a positive significant effect on Customer Satisfaction and has nosignificant effect CCB. It means that for strengthen CCB, onlinetransportation should create customer satisfaction. Research also found thatCustomer Satisfaction has a positive effect on CCB. The implication of theresearch is online transportation should improving the relationship qualityand value for creating customer satisfaction for strengthening CCB. Customersatisfaction is an important conditions for improving CCB.